2005
DOI: 10.1177/154405910508401111
|View full text |Cite
|
Sign up to set email alerts
|

X-ray Microanalysis of Elements in the Masticatory Muscle after Paresis of the Right Masseter

Abstract: Muscle activity and function appear to be related to ionic concentrations in the muscle. We investigated whether muscle paresis induced by injection of Botulinum toxin A (Botox) in 16-week-old pigs over a 56-day period is associated with ionic changes in the affected muscles. Tissue samples were taken from the masseter, temporalis, medial pterygoid, and geniohyoid muscles by a standardized method and used for energy-dispersive x-ray microanalysis in an environmental scanning electron microscope. The largest in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 16 publications
(19 reference statements)
0
5
0
Order By: Relevance
“…It is more difficult to explain why Gedrange et al showed mild but significant effects of BoNT‐A in the masseter, even though the dosage was the same (100 units/muscle) and the animals approximately the same age as ours. Importantly, this group examined biochemical rather than functional parameters.…”
Section: Discussionmentioning
confidence: 54%
“…It is more difficult to explain why Gedrange et al showed mild but significant effects of BoNT‐A in the masseter, even though the dosage was the same (100 units/muscle) and the animals approximately the same age as ours. Importantly, this group examined biochemical rather than functional parameters.…”
Section: Discussionmentioning
confidence: 54%
“…The physical changes in normal, healthy muscle tissues and subsequent repair or damage is in large controlled by key elements such as potassium, sodium, magnesium, sulfur, and calcium, and significant changes in the intracellular concentrations of any of these elements could have profound and lasting effects on the cell in PAD muscle tissue (2630). The presence and distribution of these elements also influence the electrical properties of the cell by creating electrochemical concentration gradients (31), and control its osmolarity.…”
Section: Discussionmentioning
confidence: 99%
“…Its importance is highlighted in the sodium potassium pump, or Na + /K + -ATPase, which functions to maintain the cells resting membrane potential, thus affecting the membrane permeability to various ions. The potassium potential across the cell membrane causes faster depolarization, which speeds up the rate that the muscle fiber contracts (31). It also plays a significant role in regulating cell signaling pathways, as well as control of calcium concentrations inside the cell.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, in healthy subjects with normal function, the determination of mandibular mobility is considered to be an essential part of any physiologic study of the stomatognathic system. 16 , 17 Posselt 18 defined the border movements of the mandible. Functional mandibular movement differs from border movement.…”
Section: Introductionmentioning
confidence: 99%